1990
DOI: 10.1084/jem.171.6.1943
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of murine experimental allergic encephalomyelitis with T cell receptor V beta-specific antibodies.

Abstract: Experimental allergic encephalomyelitis (EAE)' is an autoimmune disease of the central nervous system (CNS) that is induced by immunization of susceptible animal strains with myelin basic protein (MBP). The disease is characterized by lymphocyte infiltration leading to CNS lesions, demyelination, and chronic relapsing paralysis, which are symptoms similar to those seen for multiple sclerosis (MS) in humans (1-6). Prevention of EAE by treatment with CD4-specific antibodies (7,8) and adoptive transfer of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(54 citation statements)
references
References 31 publications
5
49
0
Order By: Relevance
“…Several lines of evidence support our contention. Similar to this study using TLD-4A2 mAb, several earlier reports have demonstrated EAE inhibition using purified mAb against a series of immunologically important molecules including: MHC class II molecules (Sriram and Steinman, 1983;Steinman et al, 1981), the T cell receptor (Zaller et al, 1990), CD4, ICAM-1 (Archelos et al, 1993), VLA-4 (Baron et al, 1993;Kent et al, 1995;Yednock et al, 1992) CR3 (Huitinga et al, 1993), CD28 , and the CD40L (gp39) (Gerrotse et al, 1996). Yet all of these other molecules have molecular weights, cellular distributions, and flow cytometry profiles distinct from the 4A2 molecule.…”
Section: Williams Et Alsupporting
confidence: 60%
See 2 more Smart Citations
“…Several lines of evidence support our contention. Similar to this study using TLD-4A2 mAb, several earlier reports have demonstrated EAE inhibition using purified mAb against a series of immunologically important molecules including: MHC class II molecules (Sriram and Steinman, 1983;Steinman et al, 1981), the T cell receptor (Zaller et al, 1990), CD4, ICAM-1 (Archelos et al, 1993), VLA-4 (Baron et al, 1993;Kent et al, 1995;Yednock et al, 1992) CR3 (Huitinga et al, 1993), CD28 , and the CD40L (gp39) (Gerrotse et al, 1996). Yet all of these other molecules have molecular weights, cellular distributions, and flow cytometry profiles distinct from the 4A2 molecule.…”
Section: Williams Et Alsupporting
confidence: 60%
“…mAb to interfere with T cell/endothelial cell or T cell/APC interactions and thereby block EAE induction (Baron et al, 1993;Brostoff and Mason, 1984;Kent et al, 1995;Sloan et al, 1992;Sriram and Roberts, 1986;Sriram and Steinman, 1983;Yednock et al, 1992;Zaller et al, 1990). With notable exceptions, few studies have investigated the mechanism(s) by which this EAE inhibition occurred (Bauer et al, 1995;Kent et al, 1995;Yednock et al, 1992).…”
Section: Williams Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from murine models of asthma that T cell subsets bearing different Vb chains show differences in their cytokine production, which in turn may lead to functional differences of the T cell subpopulations [16,17]. A similar observation has been made in experimental allergic encephalomyelitis in the mouse, where the pathological response can be modulated by using monoclonal antibodies to eliminate particular T cell subpopulations [18]. We hypothesized that human blood and BAL T cell subsets bearing various TCR-Vb genes might show selective differences in their cytokine profile compared to one another and to the overall T cell population.…”
Section: Discussionmentioning
confidence: 73%
“…It is feasible that QRRAA at positions 70-74 ofthe HLA-DRpi T cells with a distinct antigen specificity express, molecule, a region involved in T cell recognition in terms of V gene usage, a restricted Tcr reper- (4) toire. This could possibly be a target site for A characteristic feature ofthe rheumatoid specific immune intervention in human autoimsynovium is an intense lymphoeytie infiltration mune disease, if particular receptors are indeed (5) consisting mainly of T cells which express involved in the development of autoimmunity, class II MHC antigens (6), CD4 (7) animal model of human multiple sclerosis, by vaccination with monoclonal antibodies directed against specific Tcr Vp chains (13).…”
Section: Introductionmentioning
confidence: 99%